Studi Perbandingan antara Strategi Pembelajaran Crossword Puzzle dan Word Square terhadap Hasil Belajar IPA kelas III SD Muhammadiyah 3Nusukan Surakarta Tahun 2015 / 2016 - Nawangsari, Prahesti, Drs. Suwarno, S.H., M.Pd (2016)
The purpose of this research is 1) Knowing perbedan strategy with Word Crossword Puzzle Square on learning outcomes of the IPA on third-grade students of SD Muhammadiyah Surakarta 3 Nusukan Year 2015/2016. 2) Knowing more effective strategy of using the strategy with Word Crossword Puzzle Square to the learning outcomes IPA IPA on third-grade students of SD Muhammadiyah Surakarta 3 Nusukan Year 2015/2016. The population is all students of class III A, which consist of 40 students and III B which numbered 40 students of SD Muhammadiyah Surakarta 3 Nusukan Academic Year 2015/2016 and the sample grade students who are 40 students IIIA and IIIB numbering 40 students of SD Muhammadiyah Surakarta 3 Nusukan Academic year 2015/2016. Analysis of the data using the t test, preceded by the prerequisite test is a test of normality and homogeneity test. Based on the analysis, there is a difference between a strategy with the strategy Crossword Puzzle Word Square on learning outcomes IPA Class III SD Muhammadiyah Surakarta 3 Nusukan Year 2015/2016 can be accepted. It is shown Value tcount> t table (4.489> 2.021). The conclusion of this study were 1) There is a difference between a strategy with the strategy Crossword Puzzle Word Square on learning outcomes IPA Class III SD Muhammadiyah Surakarta 3 Nusukan Year 2015/2016 can be accepted. 2) Strategy Puzzle Corssword greater influence in improving learning outcomes IPA Class III SD Muhammadiyah 3 Nusukan, Surakarta Year 2015/2016.